Computer Aided System for Superfinishing Process Control. (2016) - Mikolajczyk, Tadeusz; Fas, Tomasz; Kłodowski, Adam; Matuszewski, Maciej; Olaru, Adrian; Olaru, Serban
Abstract: Superfinishing is one of the techniques ensuring a very low value of surface roughness of the most common external assets. The roughness of the obtained surfaces depends on the proper selection of the abrasive material and processing parameters. Yield in superfinish machining with oscillating tool depends largely on the kinematics of the oscillating movement trajectory. The paper presents the superfinishing control system based on frequency control strategy of the oscillating motion. System was developed to study the process of the controlled oscillation frequency of a grinding tool. Frequency control was enabled by the use of an inverter which provided input to the motor that drives the oscillating head. A system for automatic frequency control of the oscillating motion using computer was developed. The inverter was connected via an analog to digital interface to a PC. Dedicated control software in Visual Basic was made for this purpose. Therefore, a single system for controlling a two-stage superfinishing process has been created. This ensured quality implementation of the optimal well-known method for processing. The presented control system provides wide possibilities for control of the surface grinding, and creates opportunities for further research in determining optimal grinding conditions.